Perceived challenges to achieving universal health coverage: a cross-sectional survey of social health insurance managers/administrators in China. Issue 5 (2nd June 2017) - Shan, Linghan; Wu, Qunhong; Liu, Chaojie; Li, Ye; Cui, Yu; Liang, Zi; Hao, Yanhua; Liang, Libo; Ning, Ning; Ding, Ding; Pan, Qingxia; Han, Liyuan
Abstract : Objective: China has achieved over 96% health insurance coverage. However, universal health coverage (UHC) entails population coverage and the range of services covered and the extent to which health service costs are covered. This study aimed to determine the performance of the health insurance system in China in terms of its role in UHC and to identify challenges in the progress of UHC as perceived by health insurance managers/administrators. Methods: A cross-sectional questionnaire survey was conducted in Beijing, Ningbo, Harbin and Chongqing over the period of 2014 and 2015. A stratified cluster random sampling strategy was adopted to select study participants. A total of 1277 (64.8%) respondents who reported familiarity with the current health insurance system and the requirements of UHC provided valid data for analyses. They gave a rating on the role of the current health insurance system in achieving UHC. A multivariate logistic regression model was developed to determine the associations between the rating and the features of insurance arrangements. Results: There was consensus among the respondents on the performance of the current health insurance system in terms of its role in UHC, regardless who they were and what responsibility they held in their organisation (ie, policy development, managing fund transactions, and so on). Overall, about 45% of the respondents believed that there is a long way to go to achieve UHC. The low rating was found to be associated with limited financial protection (OR=1.656, 95% CI 1.279 to 2.146), healthcare inequity (OR=1.607, 95% CI 1.268 to 2.037), poor portability (OR=1.347, 95% CI 1.065 to 1.703) and ineffective supervision and administration of funds (OR=1.339, 95% CI 1.061 to 1.692) as perceived by the respondents. Conclusion: Health insurance managers/administrators in China are pessimistic about the achievements of the current health insurance system. They are concerned about the overall lack of benefit that insurance programmes bring to members, including low levels of entitlements, large healthcare inequity, limited financial protection and poor portability. A singular amendment of the structural design of the existing funds may not be enough to offer a satisfactory solution to these identified barriers. There is a need to increase funding capacities, to develop unified and consistent policies and to increase the level of fund pooling.